Geographic and sociodemographic variation of cardiovascular disease risk in India: a cross-sectional study of 797,540 adults - Geldsetzer, Pascal; Bärnighausen, Till (PLoS medicine, 2018)
Background Cardiovascular disease (CVD) is the leading cause of mortality in India. Yet, evidence on the CVD risk of India’s population is limited. To inform health system planning and effective targeting of interventions, this study aimed to determine how CVD risk—and the factors that determine risk—varies among states in India, by rural-urban location, and by individual-level sociodemographic characteristics. Methods and findings We used 2 large household surveys carried out between 2012 and 2014, which included a sample of 797,540 adults aged 30 to 74 years across India. The main outcome variable was the predicted 10-year risk of a CVD event as calculated with the Framingham risk score. The Harvard-NHANES, Globorisk, and WHO-ISH scores were used in secondary analyses. CVD risk and the prevalence of CVD risk factors were examined by state, rural-urban residence, age, sex, household wealth, and education. Mean CVD risk varied from 13.2% (95% CI: 12.7%-13.6%) in Jharkhand to 19.5% (95% CI: 19.1%-19.9%) in Kerala. CVD risk tended to be highest in North, Northeast, and South India. District-level wealth quintile (based on median household wealth in a district) and urbanization were both positively associated with CVD risk. Similarly, household wealth quintile and living in an urban area were positively associated with CVD risk among both sexes, but the associations were stronger among women than men. Smoking was more prevalent in poorer household wealth quintiles and in rural areas, whereas body mass index, high blood glucose, and systolic blood pressure were positively associated with household wealth and urban location. Men had a substantially higher (age-standardized) smoking prevalence (26.2% [95% CI: 25.7%-26.7%] versus 1.8% [95% CI: 1.7%-1.9%]) and mean systolic blood pressure (126.9 mm Hg [95% CI: 126.7-127.1] versus 124.3 mm Hg [95% CI: 124.1-124.5]) than women. Important limitations of this analysis are the high proportion of missing values (27.1%) in the main outcome variable, assessment of diabetes through a 1-time capillary blood glucose measurement, and the inability to exclude participants with a current or previous CVD event. Conclusions This study identified substantial variation in CVD risk among states and sociodemographic groups in India—findings that can facilitate effective targeting of CVD programs to those most at risk and most in need. While the CVD risk scores used have not been validated in South Asian populations, the patterns of variation in CVD risk among the Indian population were similar across all 4 risk scoring systems.
Gesehen am 11.12.2019